Recent Advances In Interventional Pain Management - Ratri Dwi Indriani; Dedi Susila; Muzaiwirin; Muhammad Ainur Rosyid Ridho; Abdurrahman (Indonesian Journal of Anesthesiology and Reanimation, 2024)
Introduction: Due to limited access to therapy, 60 million individuals worldwide suffer from chronic pain, with a frequency of 20–25% in some nations. Low- and middle-income countries (LMICs) are disproportionately affected by this condition. The yearly cost of diabetes, cancer, and heart disease—including medical expenses, lost productivity, and disability programs—is less than that of pain complaints. Pain management techniques, the most recent discoveries in pain research, and the most recent advancements in pain therapy technology can work together to reduce the prevalence of chronic pain and lessen the financial burden that comes with pain syndrome. Objective: To determine the extent to which the latest technological developments in interventional pain management to personalized treatment techniques according to patient complaints and conditions. The scope of technological development here is not only pain intervention techniques but also advances in understanding the pathophysiology of pain, nerve and tissue regeneration, as well as the modalities of technology used for pain interventions. Review: By conducting literature searches including journals, systematic reviews, library surveys, and case reports from the last 10 years on the latest interventional pain management techniques and serial cases. Summary: Many new minimally invasive pain intervention techniques have been developed and used in the treatment of chronic pain within the past 10 years. The necessity for standardization of processes, safety, efficacy, cost, and accessibility to new technology and techniques are among the issues and debates surrounding technical advancements and strategies for managing chronic pain. Intervention pain management techniques have grown in importance as a less intrusive method of treating chronic pain. For optimal outcomes, used in conjunction with other pain management modalities such as medication, physical therapy, cognitive behavioral change therapy, and others.